2022
DOI: 10.3390/atmos13071000
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Preventive Measures on Subjective Symptoms and Antigen Sensitization against Japanese Cedar, Cypress Pollen and House Dust Mites in Patients with Allergic Rhinitis: A Retrospective Analysis in the COVID-19 Era

Abstract: For >2 years, Japan’s government has been urging the populace to take countermeasures to prevent COVID-19, including mask wearing. We examined whether these preventive behaviors have affected the rate and degree of sensitization against pollen and house dust antigens in patients with allergic rhinitis. We retrospectively surveyed 2565 patients who had undergone allergy blood testing during the period 2015–2021. We subdivided this period into eras based on the COVID-19 pandemic: the pre-COVID (2015–2019, n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Four provided papers discuss the new type of experimental work. Oda et al [13] examined the different approaches undertaken in Japan to prevent COVID-19 against pollen and house dust antigens in patients with allergic rhinitis. The study found that 47.5% of the pollinosis patients reported improvement in nasal symptoms after the three seasons of pollen dispersion in the COVID-19 era based on the clinical records of the patients.…”
mentioning
confidence: 99%
“…Four provided papers discuss the new type of experimental work. Oda et al [13] examined the different approaches undertaken in Japan to prevent COVID-19 against pollen and house dust antigens in patients with allergic rhinitis. The study found that 47.5% of the pollinosis patients reported improvement in nasal symptoms after the three seasons of pollen dispersion in the COVID-19 era based on the clinical records of the patients.…”
mentioning
confidence: 99%